Adverse effects due to changes in the composition of the intestinal microbiota as result of the administration of antibiotics during the perinatal period - Cristina Mihaela Ghiciuc; Ionela-Alina; Diana-Cezarina Petrescu; Andrei Gheorghe Vicovan; Ioana Maria Onofrei; Ioana Rosca (Amaltea Medical Publishing House, 2022)
Antibiotic administration commonly induces allergic reactions, dysmicrobism and microbial resistance, but longterm effects due to changes in gut microbiota composition are difficult to assess. This paper aims to identify in the literature adverse effects induced by changes in gut microbiota composition after perinatal administration of antibiotics. Antibiotic administration during pregnancy is a predisposing factor for the development of bronchial asthma, eczema, or allergic rhinitis in children, but does not support the hypothesis as being a risk factor for childhood obesity/overweight. The effect on the newborn's microbiota of prophylactic administration of antibiotics during caesarean section is controversial. Postnatal treatments with antibiotics frequently causes intestinal dysmicrobism, the most severe form being necrotizing enterocolitis, especially among premature infants, but effects on the changes in body weight are controversial. Early administration of broad-spectrum antibiotics, particularly macrolides and cephalosporins, is strongly associated with the development of bronchial asthma at age 5 years. Recently, altered auditory processing and changes in recognition memory were described in newborn exposed to antibiotics in the absence of infection. More studies are needed to clarify the association between the type of antibiotic, the frequency, respectively period (both prenatal and intrapartum) of administration and long-term effects.